Contributions of Cucumis L. Genetic diversity to phytochemical bioavailability and its impact on human health: A review - Silva, Clemilson Elpidio da; Clerici, Maria Teresa Pedrosa Silva (Food Science and Technology, 2025)
The genus Cucumis L., belonging to the Cucurbitaceae family, is home to a diversity of species of economic and nutritional importance, with cucumber (C. sativus L.), melon (C. melo L.), maxixe (C. anguria L.), and kiwano melon or horned cucumber (C. metuliferus E.) being the best-known species in Brazil. These fruits represent a significant source of nutrients and ingredients for the food, pharmaceutical, and ethnopharmacological industries. This article provides an overview of the chemical characteristics, nutritional composition, and applications of the genus Cucumis L., addressing its diversity, geographical distribution, economic importance, traditional and potential uses, as well as the challenges and future prospects for research and development of new products.